Double Walled Polymeric Drug Delivery Systems Containing Nanoparticle Drug Intended for Colon-Specific Delivery - OMID RANAEI SIADAT, SEYED; MAHKAM, MEHRDAD; MOHAMMADI, REYHANEH (Asian Journal of Chemistry, 2010)
Double walled polymer with a Core of mixture of nanoparticle of carboxymethyl cellulose sodium salt and a model drug olsalazine [3,3´-azobis(6-hydroxy benzoic acid)] as an azo derivatives of 5-aminosalicylic acid and an external coat of cross-linked copolymers of N-vinyl-2-pyrrolidinone and methacrylic acid with various amounts of cross-linking agents. Cubane-1,4-dicarboxylic acid linked to two HEMA group is the cross-linking agent. The core nanocomposite was prepared by freeze drying method and then used as nuclei for subsequent sell copolymerization. The structure of core was characterized with scanning electron microscopy. The doublewalled hydrogels were characterized by differential scanning calorimetry and FT-IR. Equilibrium swelling studies were carried out in enzyme-free simulated gastric and intestinal fluids. The drug-release profiles indicated that the amount of drug released depend on the degree of swelling. The swelling was modulated by the amount of crosslinking in shell layer. Based on the great difference in hydrolysis rates at pH 1 and 7.4, these pH-sensitive hydrogels appear to be good candidates for colon-specific drug delivery.